Effects of crop evolution under domestication and narrowing genetic bases of crop species - Temesgen Begna (Open Journal of Plant Science - Peertechz Publications, 2021)
Crop improvement is very crucial to satisfy the world demand in the presence of different challenges like climate change, reducing arable land and increasing population growth. Crop improvement program is continuously striving to increase crop yield, enhance crop quality and improve crop tolerance to biotic and abiotic stresses. Domestication has a great role in increasing agricultural productivity through selecting suitable crop plants to human beings like high yielding varieties with resistance to biotic and abiotic stresses, improved nutritional quality, big seed and fruit size, non-shattering, reduction of seed dispersal mechanisms, a more compact growth habit, early matured crop plants. Domesticated food crops are derived from a phylogenetically diverse assemblage of wild ancestors through artificial selection for different traits. Plant breeding and domestication of crop plants have a profound impact on the genetic diversity through selecting the desirable crops by neglecting other crop plants with undesirable traits. Domestication of crop plants shifted from hunter-gatherer to agricultural societies which leaded the rise of modern civilization. The amount or quantum of genetic diversity available in a breeding population is referred to as genetic base of that population. In other words, genetic base represents spectrum of genetic variability in a plant breeding population. Depending upon the amount of genetic diversity present in a plant breeding population, genetic base is of two types, viz. broad genetic base and narrow genetic base. Plant populations that are composed of several pure lines, inbred lines or heterozygotes and homozygotes are said to have broad genetic base. Examples of such populations are mass selected varieties, multiline varieties, synthetics, composites and land races. Such genotypes have wider adaptation to environmental changes. Those plant populations that have been developed from single homozygote or heterozygote are-said to have narrow genetic base. Examples of such populations are pure line variety, varieties developed by backcross, pedigree method bulk method, and single seed decent method, clonal variety and hybrids between two inbred lines or pure lines. Genetic loss is directly connected with the reduction of genetic diversity including the loss of individual genes and as well as the loss of particular combinations of genes such as those manifested in locally adapted landraces. Eventually, genetic erosion is the depletion in population variation because of inbreeding and genetic drift which is largely causes the endangerment of small isolated populations. Narrowing of genetic diversity might result the complete loss of crop plants.